Political Soldiers of the Party: A Political and Social Portrait of the KGB Cadre - Burinskaitė, Kristina (Genocidas ir rezistencija, 2024)
The KGB cadres are undeservedly left in the shadow of the agents, even though they were the ones who implemented the repressive policy, persecuted and interrogated individuals, and recruited agents and formed assignments for them. The Soviet security worker before and after 1953 differed, because the new challenges did not require the brutality characteristic of the Stalinist period, but rather – greater intellectual capacities, so the number of Lithuanians and people with high educational attainment on the staff increased. However, the social and political portrait of a member of the Cheka was no less influenced by the status of this structure itself, because a job with the KGB was prestigious and privileged, and formed a certain status of secretiveness and exclusiveness.
Keywords: KGB; cadres; communist ideology; Communist Party; social portrait